The Second Edition of the Milan System for Reporting Salivary Gland Cytopathology: System Application, Outcome, and Cytohistological Correlation - Magdalena Onyszczuk; Bogna Drozdzowska (Journal of Cytology)
Background:Fine needle aspiration (FNA) cytology for salivary gland lesions is sensitive and specific for diagnosing and treating salivary gland pathologies. The objective of the Milan System for Reporting Salivary Gland Cytopathology (MSRSGC) is to organize the diagnostic information from the FNA into a uniform reporting terminology.